Species delineation in the speciation grey zone—The case of Diopatra (Annelida, Onuphidae) - Elgetany, Asmaa H.; van Rensburg, Hendré; Hektoen, Martin; Matthee, Conrad; Budaeva, Nataliya; Simon, Carol A. & Struck, Torsten H (Zoologica Scripta, 2020)
Taxonomy based on morphology can be difficult. The challenges arise from different sources such as poor original descriptions, new records based on inadequate knowledge, uncritical application of general assumptions or presence of complexes of cryptic species. One example of problematic taxonomy is the genus Diopatra Audouin & Milne Edwards, 1833 (Onuphidae, Annelida) and within it the two species Diopatra aciculata and D. neapolitana. The species exhibit great similarity between them casting doubts on their validity as separate species. Our study aims to investigate whether D. aciculata and D. neapolitana should be synonymized, using an integrative taxonomic approach. Therefore, we assessed 22 morphological characters of 70 specimens including one specimen, which might have been erroneously assigned to D. dentata. Additionally, sequence information of five different molecular markers (i.e., 16S rDNA, COI, 28S, ITS1 and ITS2) was gathered to delineate possible species boundaries between these two species. Our results show some evidence for delineating the two species, but they are not conclusive due to both presence of shared morphological characters and conflicting evidence in the molecular data. Accordingly, our results neither confirm nor disprove complete speciation and both species seem to be in the grey zone of speciation. In conclusion, considering taxonomic stability and slight support by morphological characters, we still regard each as two independent species.
World Polychaeta Database (WPolyDb)